Strategi Kebijakan Akselerasi Sertifikasi Halal Bagi Usaha Mikro, Kecil, dan Menengah (UMKM) di Provinsi Kalimantan Timur Menyongsong Ibu Kota Negara (IKN) Nusantara - Rudi Kartono (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
East Kalimantan Province, as the main buffer for the Nusantara National Capital City (IKN), faces both significant challenges and opportunities in local economic development, especially for Micro, Small, and Medium Enterprises (UMKM). The increase in population and demand in IKN will be dominated by the halal product market, given that the majority of Indonesia's population is Muslim. However, the level of halal certification ownership among UMKM in East Kalimantan remains low. This policy paper aims to analyze the problems in accelerating halal certification and to formulate an effective policy strategy. The background highlights the gap between the large potential of the halal market and the reality of its implementation, which is constrained by various factors. The problem formulation focuses on the ineffectiveness of socialization and education, as well as the limited reach of halal assistants and counselors. The writing methodology uses a qualitative approach with secondary data analysis from various reliable sources and policy analysis. The results of the analysis indicate that the root of the problem lies in human resources (assistants), methods (socialization), regulations (complexity), and the environment (UMKM awareness). Based on USG and Fishbone analysis, the main problems are the lack of reach and effectiveness of assistance. The conclusion of this analysis is that without targeted policy intervention, East Kalimantan's MSMEs will struggle to compete in the IKN market